The Impact of Strategic Operations Management Decisions on Shoppers’ Wellbeing - Demir, Ahmet (Asian Academy of Management Journal, 2019)
Various studies have looked at the operations management field in shopping malls, but the impact of strategic decision areas on shoppers’ wellbeing in malls has not been explored. This study elaborates the importance of structural and infrastructural decision areas for shoppers’ wellbeing in malls. Since operations management is one of three vital departments (along with marketing and finance) of most organisations, it is important to examine how decisions in operations management of shopping malls impact shoppers’ wellbeing. This paper examines the structural and infrastructural decision-areas made by shopping mall operations managers in the Kurdistan Region of Iraq to see how they impact shoppers’ wellbeing. A survey questionnaire was administered to 575 shopping mall customers. IBM SPSS 23 was used to conduct exploratory factor analysis and hierarchical regression analysis. Additionally, an IBM AMOS 23 was used to conduct structural equation modelling. The results indicate that both the structural and infrastructural decision areas of operations management are significantly important in determining shoppers’ wellbeing. The variance of shoppers’ wellbeing in each strategic decision area is further explained. The findings of this study consist of implications for researchers and especially for practitioners. The study constructs a framework for future studies about how the operations strategic decision areas impact shopper wellbeing in malls. Furthermore, practitioners can use the findings of this study when they perform their strategic planning. Finally, those developments would influence consumers’ wellbeing during their visits to shopping malls.